It Takes a Village: A Social Network Approach to NGOs' International Public Engagement. (November 2019) - Saffer, Adam J.; Yang, Aimei; Morehouse, Jordan; Qu, Yan
Nongovernmental organizations (NGOs), like most strategic communicators, are challenged with breaking through the saturated international media environment as they attempt to influence public opinion. Yet, before strategic communicators can build an agenda, they must get attention from the public. The current study examined how NGOs' network positions in the public Twitter discussion of the global refugee crisis influenced the public engagement NGOs received during two news events. Drawing from network theory and research, we posed two parallel sets of hypotheses. First, we predicted that NGOs with characteristics of "star" network structures will be well-situated in the network to garner attention. Second, we hypothesized that the "village" around an NGO also contributes to capturing attention. The results from our regressions offer evidence to support both hypotheses.